The complete mitochondrial genome of Paecilomyces hepiali (Ascomycota, Eurotiomycetes). (3rd March 2016) - Wang, Linping; Xu, Jiayue; Li, Huchen; Song, Lipu; Yu, Yi; Zhang, Wensheng; Liu, Guiming; Feng, Chengqiang
Abtract: Paecilomyces hepiali, belonging to the Eurotiales order Ascomycota, is an endoparasitic fungus that commonly exists in the natural Cordyceps sinensis anamorph stage. Here, we report the complete mitochondrial DNA sequences of P. hepiali for the first time. The genome is 24, 245 bp in length, encoding 15 protein-coding genes (PCGs), 2 rRNA genes, 25 tRNA genes and 3 homing endonucleases. The overall AT composition is 73.37% and the average AT content of PCG, rRNA, tRNA and non-coding region are 74.21%, 66.07%, 62.83% and 75.96%, respectively. Phylogenetic analysis with eight Ascomycota species and thirteen Basidiomycota species revealed that P. hepiali is was more closely related to Cordyceps bassiana, Cordycep smilitaris and Cordyceps brongniartii . It is confirmed that P. hepiali is a derivative of Cordyceps sinensis . This study provided valuable information on the gene contents of the mitochondrial genome and would facilitate the study of function and evolution of P. hepiali .